Outcome Metrics in the Treatment of Distal Radius Fractures in Patients Aged Above 50 Years: A Systematic Review. (December 2022) - Fogel, Nathaniel; Mertz, Kevin; Shapiro, Lauren M.; Roe, Allison; Denduluri, Sahitya; Kamal, Robin N.
Background: The inclusion of patient-reported outcome measures (PROMs) serves to better quantify aspects of patient outcomes missed with objective measures, including radiographic indices and physical examination findings. We hypothesize that PROMs are inconsistently and heterogeneously captured in the treatment of distal radius fractures. Methods: We performed a systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines of all level I and II randomized controlled trials (RCTs) of distal radius fracture treatment of any modality for those older than 50 years of age from January 2008 to January 2018. A total of 23 studies were included in the final analysis. The metrics used by each study to assess outcomes were collected, compared, and described. Results: Physical examination findings and radiographic measures were reported in 70% and 74% of studies, respectively. Patient-reported outcomes measures were used to assess outcomes in 74% of studies. Only the Disabilities of the Arm, Shoulder, and Hand was used in greater than half of the studies (57%). Pain scores were assessed in 39% of studies and complications in only 26%. Conclusions: There is substantial heterogeneity and lack of standardization in the collection of both objective outcome measures and PROMs in level I and II RCTs for the treatment of distal radius fractures. The ability to compare between studies or aggregate data among studies is therefore limited. Radiographic and physical examination findings remain frequently reported despite known limitations of these metrics. The routine collection of PROMs after the treatment of distal radius fractures can ensure care is directed toward improving what is most important to patients.